Evaluation of the dispersants effectiveness using the Baffled Flask Test - Grechishcheva, Natalia; Kuchierskaya, Alexandra; Semenov, Anton; Kuryashov, Dmitry; Meritsidi, Irakli; Mingazov, Rifat (Journal of Environmental Engineering and Landscape Management, 2022)
The use of chemical dispersants is one of the most widely used methods for responding to oil spills. The most important characteristic of dispersants is their effectiveness. The dispersant effectiveness is a measure of how well the dispersant breaks up and stabilizes the oil into the water column. In this paper, we studied the dispersing ability of three proprietary dispersants with respect to light and heavy crude oils of Usinsk and Nagornoye fields with a density of 0.816 g/cm3 and 0.896 g/cm3, respectively. The dispersant effectiveness was determined using a Baffled Flask Test; dispersant was applied to the oil slick, mixed, and the concentration of oil in a sample taken from the water column was measured using UV-Visible spectrophotometry. A modification of the standard technique is proposed to minimize the error of the method for the heavy crude oil by eliminating the error associated with inaccuracy of dosing. For this purpose, oil of the Nagornoye field was added to the tested systems not “by volume”, but “by weight”. It was provided better convergence of the experimental results. The standard deviation in the case of dosing of oil “by volume” exceeded 10% and varied from 11.87% to 13.59%. The introduction of oil “by weight” was much lower and varied from 5.66% to 6.30%. Studied dispersants have a higher dispersing ability for the less dense oil of the Usinsk field.